The Blue Ocean Strategy Revisited: What Colour Will the Ocean Be Tomorrow? - Cezar SCARLAT; Dan-Andrei PANDURU (Communications of International Proceedings, 2021)
The history of scientific management that started a hundred years ago culminated in the second part of the last century with successful theories on strategic management, associated with dominant figures of scholars, as well as concepts as strategy, strategic thinking, strategic planning and strategic plan – so that strategic management was the norm. The politico-economic environment at a millennia border, characterized by dissolution of many centrally planned economies and global crises, has demonstrated that rigidity associated with strategic planning do not provide universal solutions. Thus, more flexible schools of strategic thought started to gain ground: the Blue Ocean strategy among them. Besides models and tools for analysing the current situation and trying to find the best strategic move from the current red ocean of fierce competition to the much-desired serene blue ocean (where competition becomes irrelevant because new markets are created), the Harvard scholars who have developed the Blue Ocean strategy have further elaborated guidelines and tools to be used in the process of this transition, seizing that this transition process is not easy. Following several situations observed, in which the practical transition proved to be more difficult than expected in theory, this paper aims at opening a discussion exactly on the issue of, metaphorically, the colour of the ocean of the current competitive market: as not being red anymore nor blue yet; likely being a “purple ocean”. The managerial implications are important for scholars and researchers, as well as for practitioners – strategy makers and top business managers mainly.
Keywords: Strategic Thinking; Strategic Management; Blue Ocean; Purple Ocean.